MOTIVASI PETANI DALAM USAHATANI PADI DI SAWAH TADAH HUJAN DI KAPANEWON JETIS BANTUL DIY - Nofianto, Irman; Astuti, Ari; Ratri, Wahyu Setya (JURNAL ILMIAH AGRITAS, 2024)
The research was conducted to analyse the motivation of farmers in rice farming in rainfed paddy fields in Kapanewon Jetis, Bantul, Yogyakarta. The research method used is descriptive quantitative method, the determination of the location is done by (purposive method). The sample was 57 farmer respondents using the census method. The types of research data are primary and secondary data. Data analysis using descriptive analytical method with hypothesis testing using t test. The results showed the factors that influence the motivation of farmers are internal factors consisting of the age of respondents 45-64 years (52.6%). The highest number of family dependents 3-4 people (17.50%). Farming experience >10 years (91.2%). Average land ownership status is freehold (63.2%). The average land size was 800-1299m² (38.6%). There were (19.2%) respondents who had an income of more than the Bantul Regency minimum wage of IDR 2,066,000. External factors consisted of family encouragement in the form of labour assistance (89.4%), and environmental factors related to rice-paddy-cropping patterns (89.4%). The Existence motivation level is in the medium category with an average score of 2.04, Relatedness in the high category with an average score of 2.37 and, Growth in the high category with an average score of 2.32. The level of motivation (ERG) is in the medium category with an average score of 2.24.  The results of hypothesis testing show that the motivation of farmers in rice farming in rainfed paddy fields in Kapanewon Jetis Bantul Yogyakarta is low. Keywords: Motivation, Existence, Relatedness, Growth, Rainfed.